Lipotoxic Impairment of Mitochondrial Function in β-Cells: A Review - Axel Römer; Thomas Linn; Sebastian F. Petry (MDPI AG, 2021)
Lipotoxicity is a major contributor to type 2 diabetes mainly promoting mitochondrial dysfunction. Lipotoxic stress is mediated by elevated levels of free fatty acids through various mechanisms and pathways. Impaired peroxisome proliferator-activated receptor (PPAR) signaling, enhanced oxidative stress levels, and uncoupling of the respiratory chain result in ATP deficiency, while β-cell viability can be severely impaired by lipotoxic modulation of PI3K/Akt and mitogen-activated protein kinase (MAPK)/extracellular-signal-regulated kinase (ERK) pathways. However, fatty acids are physiologically required for an unimpaired β-cell function. Thus, preparation, concentration, and treatment duration determine whether the outcome is beneficial or detrimental when fatty acids are employed in experimental setups. Further, ageing is a crucial contributor to β-cell decay. Cellular senescence is connected to loss of function in β-cells and can further be promoted by lipotoxicity. The potential benefit of nutrients has been broadly investigated, and particularly polyphenols were shown to be protective against both lipotoxicity and cellular senescence, maintaining the physiology of β-cells. Positive effects on blood glucose regulation, mitigation of oxidative stress by radical scavenging properties or regulation of antioxidative enzymes, and modulation of apoptotic factors were reported. This review summarizes the significance of lipotoxicity and cellular senescence for mitochondrial dysfunction in the pancreatic β-cell and outlines potential beneficial effects of plant-based nutrients by the example of polyphenols.